Philosophical Reconstruction of Restorative Justice in Indonesia: An Analysis of Procedural Asymmetry in the Perspective of Maqaṣid Al-Syari'ah - Ulil Albab; Harmoko (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
The development of the modern criminal justice system shows a paradigm shift from a retributive approach to a restorative approach that focuses on the recovery of losses, substantive justice, and the balance of interests between perpetrators, victims, and the community through restorative justice mechanisms. In Indonesia, this approach is applied in response to various weaknesses of the conventional criminal justice system, such as low recovery of victims' rights, overcapacity of correctional institutions, and limited effectiveness of prison sentences in reducing crime rates. However, the implementation of restorative justice in law enforcement practice still tends to be administrative and pragmatic, so it is more oriented towards stopping cases than substantive restoration of benefits. In practice, the victim's position is often only placed as a procedural complement, while aspects of psychological recovery, social relationship balance, and moral development of the perpetrator have not been the main concern. This study aims to analyze the concept of restorative justice from the perspective of Maqaṣid al-Syari'ah and evaluate its implementation in the criminal justice system in Indonesia. The research method used is normative legal research with a conceptual and legislative approach, which is analyzed qualitatively using the framework of Maqaṣid al-Syari'ah Jasser Auda. The results of the study show that restorative justice is substantively in accordance with the principles of Maqaṣid al-Sharia, especially in the protection of the soul (ḥifẓ al-nafs), property (ḥifẓ al-māl), and social order. However, the implementation of restorative justice regulations in Indonesia still shows procedural asymmetry because the dominance of the administrative approach of law enforcement officials has not fully guaranteed the protection of victims' rights and comprehensive social recovery. This study confirms that Maqaṣid al-Sharia is not only relevant as a normative legitimacy, but also as an evaluative framework to direct the application of restorative justice to be more just, humanistic, and oriented towards substantive benefits.